Reconstruction of the Alveolar Buccal Bone Plate in Compromised Fresh Socket after Immediate Implant Placement Followed by Immediate Provisionalization - Molon, Rafael Scaf de [UNESP]; Avila, Erica Dorigatti de [UNESP]; Borelli de Barros-Filho, Luiz Antonio [UNESP]; Ricci, Weber Adad [UNESP]; Tetradis, Sotirios; Cirelli, Joni Augusto [UNESP]; Borelli de Barros, Luiz Antonio [UNESP] (Wiley-Blackwell, 2015)
ObjectiveThe aim of this clinical report was to reestablish the buccal bone wall after immediate implant placement. The socket defect was corrected with autogenous bone, and a connective tissue graft was removed from the maxillary tuberosity to increase the thickness, height, and width of the buccal bone and gingival tissue followed by immediate provisionalization of the crown during the same operation.Clinical ConsiderationsA 66-year-old patient presented with a hopeless maxillary left central incisor with loss of the buccal bone wall. Atraumatic, flapless extraction was performed, and an immediate implant was placed in the extraction socket followed by preparation of an immediate provisional restoration. Subsequently, immediate reconstruction of the buccal bone plate was performed, using the tuberosity as the donor site, to obtain block bone and connective tissue grafts, as well as particulate bone. Finally, immediate provisionalization of the crown followed by simple sutures was performed. Cone-beam computed tomography and periapical radiographs were taken before and after surgery. After 4 months, the final prosthetic crown was made. After a 2-year follow-up, a satisfactory aesthetic result was achieved with lower treatment time and morbidity.ConclusionThis case demonstrates the effective use of immediate reconstruction of the buccal bone wall for the treatment of a hopeless tooth in the maxillary aesthetic area. This procedure efficiently promoted harmonious gingival and bone architecture, recovered lost anatomical structures with sufficient width and thickness, and maintained the stability of the alveolar bone crest in a single procedure.Clinical SignificanceIf appropriate clinical conditions exist, immediate dentoalveolar restoration may be the most conservative means of reconstructing the buccal bone wall after immediate implant placement followed by immediate provisionalization with predictable healing and lower treatment time.